The Legality Or Otherwise Of Abortion Under Islamic Law: A Case Study Of Boko Haram - Hamidu Ardo; Abubakar Ibrahim Adamu (Al-Arfa: Journal of Sharia, Islamic Economics and Law, 2026)
Interpretations regarding abortion. Abortion is generally permitted in Islam if the mother’s life is at risk or in cases of severe fetal abnormalities. However the specific gestational limit for permissibility varies among Islamic schools of thought, the concept of ensoulment, or when fetus is believes to receive a soul, is crucial in determining abortions permissibility. Some interpretations consider ensoulment to occur at conception, while others believe it happens later. Around 120 days after conception. Different schools of thought such as Hanafi, Maliki, Shafii and Hanbali have varying opinions on abortion some are more restrictive,  while others allow abortion under specific circumstances. Analytical research methodology was used in this paper. Data are drawn from books, articles, scholarly journals etc